Protein Folding - Cruzeiro, Leonor (2014)
The existing experimental data on protein folding is briefly reviewed. It is argued that the optimal fit is within a multi-funnel shaped free energy landscape and a kinetic mechanism for folding. The possibility that the transient forces responsible for such a kinetic mechanism come from vibrational excited states (the VES hypothesis) is introduced. Two applications of the VES hypothesis to the structural instability of the proteins associated with misfolding diseases are presented. Finally, in the last section, a detailed kinetic mechanism is put forward according to which, in cells, the structure that polypeptide chains adopt, as they come out of the ribosome, is a helix, and the proposed general pathway followed by all amino acid sequences from this initial structure to the final three dimensional structure is described. An analysis is made of how the proposed kinetic mechanism can account for many of the experimentally observed features of protein folding. It is pointed out how this new kinetic mechanism, which was arrived at by the application of physical principles, may also help to derive a method of determining the tertiary structure of a protein from its primary sequence.